High intensity focused ultrasound: physical principles and devices. - Haar, G; Coussios, C (2007)
High intensity focused ultrasound (HIFU) is gaining rapid clinical acceptance as a treatment modality enabling non-invasive tissue heating and ablation for numerous applications. HIFU treatments are usually carried out in a single session, often as a day case procedure, with the patient either fully conscious, lightly sedated or under light general anaesthesia. A major advantage of HIFU over other thermal ablation techniques is that there is no necessity for the transcutaneous insertion of probes into the target tissue. The high powered focused beams employed are generated from sources placed either outside the body (for treatment of tumours of the liver, kidney, breast, uterus, pancreas and bone) or in the rectum (for treatment of the prostate), and are designed to enable rapid heating of a target tissue volume, while leaving tissue in the ultrasound propagation path relatively unaffected. Given the wide-ranging applicability of HIFU, numerous extra-corporeal, transrectal and interstitial devices have been designed to optimise application-specific treatment delivery. Their principle of operation is described here, alongside an overview of the physical mechanisms governing HIFU propagation and HIFU-induced heating. Present methods of characterising HIFU fields and of quantifying HIFU exposure and its associated effects are also addressed.